Agent based syntex error detection for C programming language - Syra G Mokunjil (2013)
A lot of university students find debugging syntax errors overwhelming especially if they are novice to the world of programming language. This is because they do not know how or where to begin. Although there are enormous printed and online materials available but the information ‘overloading’ may only result in more confusion for the students in seeking for the right information. Handing the assignment manually to the faculty may pose the risk of the assignment being lost and thus, student has to redo and resubmit the assignment. On the other hand, lecturer has to spend time on mundane and repetitive task of preparing assignment questions, reminding students of submission deadline, answering queries etc. Thus, an online web-based system in Agent Based Syntax Error Detection for C Programming named Online Student Assignment Assistance System (OSAAS) is developed to automate some of the human repetitive and mundane task mentioned earlier. It applies the intelligent agent technique whereby it is able to compile the programming file through the website and directs student to the related help file upon detection of syntax error. Submission deadline reminders, simple online help search, marking and grading facilities are some of the useful features of OSAAS. Thus, it is hoped that OSAAS will encourage early assignments submission and provide greater learning satisfaction.